Do school students' academic self-concept and prior knowledge constrain the effectiveness of generating technology-mediated explanations?. (June 2022) - Jacob, Leonie; Lachner, Andreas; Scheiter, Katharina
Abstract: Asking students to generate explanations to fictitious others by means of different technologies (e.g., instant messenger, video) has gained popularity in schools. Although the potential of these technology-mediated explaining activities is appealing, less is known whether generating these explanations is effective for school students. Additionally, empirical evidence regarding general effects of learning-by-explaining proposes that generating explanations is constrained by different boundary conditions. In this experimental field study, we investigated the effectiveness of technology-mediated explaining with seventh grade students ( N  = 129). More importantly, we contrasted different implementation modalities of explaining (i.e., written versus oral explaining) and examined the moderating role of cognitive and motivational prerequisites (i.e., prior knowledge, academic self-concept). After assessing prior knowledge and academic self-concept, students attended a lesson on photosynthesis. Then, students were randomly assigned to explain the contents in written versus oral form in a mock-up messenger or to retrieve the contents by taking notes (control condition). We neither obtained an effect of explaining, nor did the explanatory modality account for students' learning. However, exploratory moderation analyses showed that academic self-concept but not prior knowledge moderated the explaining effect on comprehension, as only students with low self-concept profited from explaining. In contrast, students with high self-concept benefited most from retrieving the provided contents. The findings highlight that technology-mediated explaining is not necessarily an effective learning activity for school students, but might depend on students' motivational prerequisites, such as their academic self-concept. Highlights: In an experiment with secondary students, we explored effects of explaining. Learning-by-explaining was moderated by self-concept but not prior knowledge. Low academic self-concept students profited more from explaining than retrieval. High academic self-concept students benefited more from retrieving than explaining. There was no main effect of explaining regardless of modality.